The BURP domain protein AtUSPL1 of Arabidopsis thaliana is destined to the protein storage vacuoles and overexpression of the cognate gene distorts seed development - Le, Van Son; Hillmer, Stefan; Hinz, Giselbert (Plant molecular biology, 2009)
BURP domain proteins comprise a broadly distributed, plant-specific family of functionally poorly understood proteins. VfUSP (Vicia faba Unknown Seed Protein) is the founding member of this family. The BURP proteins are characterized by a highly conserved C-terminal protein domain with a characteristic cysteine-histidine pattern. The Arabidopsis genome contains five BURP-domain encoding genes. Three of them are similar to the non-catalytic β-subunit of the polygalacturonase of tomato and form a distinct subgroup. The remaining two genes are AtRD22 and AtUSPL1. The deduced product of AtUSPL1 is similar in size and sequence to VfUSP and that of the Brassica napusBNM2 gene which is expressed during microspore-derived embryogenesis. The protein products of BURP genes have not been found, especially that of VfUSP despite a great deal of interest arising from copious transcription of the gene in seeds. Here, we demonstrate that VfUSP and AtUSPL1 occur in cellular compartments essential for seed protein synthesis and storage, like the Golgi cisternae, dense vesicles, prevaculoar vesicles and the protein storage vacuoles in the parenchyma cells of cotyledons. Ectopic expression of AtUSPL1 leads to a shrunken seed phenotype; these seeds show structural alterations in their protein storage vacuoles and lipid vesicles. Furthermore, there is a reduction in the storage protein content and a perturbation in the seed fatty acid composition. However, loss of AtUSP1 gene function due to T-DNA insertions does not lead to a phenotypic change under laboratory conditions even though the seeds have less storage proteins. Thus, USP is pertinent to seed development but its role is likely shared by other proteins that function well enough under the laboratory growth conditions.